Forecasting Kansas land values using net farm income. Issue 1 (2nd May 2017) - Featherstone, Allen M.; Taylor, Mykel R.; Gibson, Heather
Abstract : Purpose: With the decline of US net farm income from $123.8 billion in 2013 to $71.5 billion forecasted for 2016, concern has developed regarding the future path of agricultural land values. The purpose of this paper is to examine the relationship between net farm income, cash rents and land values in the state of Kansas and provides insight regarding future land values. Design/methodology/approach: This study estimates partial adjustment models for cash rent and land values and uses those results to infer long-run capitalization rates and earnings multipliers. These models are used to forecast Kansas land values through 2018 and also the long-run price of farmland given 2016 expectations. Findings: Land adjusts to changes in Kansas net farm income slowly with a one-year elasticity of 6.7 percent. The long-run elasticity is 96.9 percent which is very close to the 100 percent suggested by the theoretical income capitalization model. The long-run multiplier for income in Kansas is 21.71 which implies a capitalization rate of 4.61 percent. The estimated results suggest that Kansas land values would peak in 2016 and begin to slowly decline. If market conditions were to remain the same, land values would ultimately decrease to $1, 171 per acre, a 28 percent decline from current levels. Originality/value: Declines of the magnitude in estimated land values could negatively affect the financial condition of the sector. Factors such as a change in the long-run capitalization rate or unexpected supply or demand shocks for agricultural commodities globally could certainly alter the long-term prospects. However, current expectations as of March 2016 suggest that farmers will face difficult conditions over the next few years.